2012
DOI: 10.1007/s00586-012-2356-2
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal balance correction of idiopathic scoliosis using the in situ contouring technique

Abstract: Purpose Idiopathic scoliosis can lead to sagittal imbalance. The relationship between thoracic hyper-and hypokyphotic segments, vertebral rotation and coronal curve was determined. The effect of segmental sagittal correction by in situ contouring was analyzed. Methods Pre-and post-operative radiographs of 54 scoliosis patients (Lenke 1 and 3) were analyzed at 8 years follow-up. Cobb angles and vertebral rotation were determined. Sagittal measurements were: kyphosis T4-T12, T4-T8 and T9-T12, lordosis L1-S1, T12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Group mean values for maximal thoracic, thoracolumbar and lumbar rotation were lower than those found in the literature 9 , 10 ; however, this may be due to the fact that scoliosis patients not reaching the indication for surgery were also included. A wider range for maximal rotation was seen than that described in previous studies, with Th4-Th5, Th11-12, and L4 vertebrae also observed.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Group mean values for maximal thoracic, thoracolumbar and lumbar rotation were lower than those found in the literature 9 , 10 ; however, this may be due to the fact that scoliosis patients not reaching the indication for surgery were also included. A wider range for maximal rotation was seen than that described in previous studies, with Th4-Th5, Th11-12, and L4 vertebrae also observed.…”
Section: Discussionmentioning
confidence: 65%
“…Kotwicki et al 9 found maxAVR was between 10 and 24 close to the T9 vertebra in Lenke 1 patients. Charles et al 10 found the maximal thoracic vertebral rotation between T6 and T10 vertebrae, with an average of 22.7 in standing position and the maximal lumbar vertebral rotation was measured at an average of 25.8 and was found at L1 and L3 vertebrae in Lenke 3 patients.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have found some abnormalities in sagittal spinal alignment such as decreased thoracic kyphosis and hypo-lordosis in patients with AIS (3,(7)(8)(9)(10). Vertebral rotation in thoracic curves forces the spinal column anterolaterally and vertebral migration in lumbar curves forces the spinal column posterolaterally (11). Considering the anatomical and biomechanical relationships among different parts of the body, it is expected that any spinal malalignment in sagittal plane cause some changes in other parts of the musculoskeletal system such as pelvis or lower extremities (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Our objective was to prove the relationship between shape of back (pelvic incidence) (PI) and parameters, which evaluate the kyphosis deformity in thoraco-lumbar trauma. Pelvic parameters defined for many years by Duval-Beaupère and legaye [17,18] are significant chain of correlations between positional pelvic and spinal parameters which are fundamental for the surgical management of spinal degenerative and malformative deformities [19][20][21]. Although, this concept is less spread in thoraco-lumbar fractures.…”
Section: Introductionmentioning
confidence: 99%